2011
DOI: 10.1007/s10165-011-0485-9
|View full text |Cite
|
Sign up to set email alerts
|

Which subgroup of rheumatoid arthritis patients benefits from switching to tocilizumab versus etanercept after previous infliximab failure? A retrospective study

Abstract: A retrospective study of 39 rheumatoid arthritis (RA) patients with an inadequate response to infliximab was conducted. The responses of subjects switching from infliximab to tocilizumab (n = 23) were compared to those of subjects switching to etanercept (n = 16). Disease activity was assessed by the Disease Activity Score 28-CRP ([C-reactive protein] DAS28-CRP), the Simplified Disease Activity Index (SDAI), and the Clinical Disease Activity Index (CDAI). Twenty-two patients completed 48 weeks of tocilizumab t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although our study protocol included all eight bDMARDs available at the time of the chart review, our final sample sizes were too small to allow for meaningful comparisons between individual bDMARDs (on average, 26 treatments per bDMARD). In other studies, responses were dependent on which bDMARDs were included in the comparisons [ 18 , 19 ]. We also did not assess the impact of choice of concomitant non-bDMARD on study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study protocol included all eight bDMARDs available at the time of the chart review, our final sample sizes were too small to allow for meaningful comparisons between individual bDMARDs (on average, 26 treatments per bDMARD). In other studies, responses were dependent on which bDMARDs were included in the comparisons [ 18 , 19 ]. We also did not assess the impact of choice of concomitant non-bDMARD on study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The RA status was evaluated at 12, 24, and 52 weeks after the initiation of GLM treatment by the serum C-reactive protein (CRP) level and erythrocyte sedimentation rate (ESR). DAS 28-ESR and DAS28-CRP were used to evaluate RA disease activity compared with baseline; the DAS28 was calculated according to the standard formula [ 14 , 15 ]. The GLM continuation rates at 52 weeks were also examined.…”
Section: Methodsmentioning
confidence: 99%
“… 14 A retrospective study reported that switching from first TNFi (infliximab) to either another MOA bDMARD (tocilizumab) or second TNFi (etanercept) in patients with RA showed no significant difference in efficacy, as measured by disease activity. 15 However, randomized controlled trials suggested that switching to non-TNFi biologic agents, such as rituximab, tocilizumab, and abatacept, could be an alternative option for RA patients with an inadequate response to one or more TNFis. 16 18 Moreover, an observational study reported that, after failure of a first TNFi for RA, switching to a new MOA bDMARD (rituximab) was more effective than cycling to another TNFi.…”
Section: Introductionmentioning
confidence: 99%